Male and Female Students' Learning Styles and Their English-speaking Skills: A Qualitative Case Study - Laili Faridah; Abd Aziz Wahab; Zainuddin Zainuddin (EDUCATION AND LINGUISTICS KNOWLEDGE JOURNAL, 2023)
In teaching English, student learning styles are factors that influence student learning tactics. learning style is an overall pattern that offers learning behavior a widespread direction. in an effort to reach their full potential, a person will expand abilties that help a person learn in a number of approaches. particularly in speaking abilities. In understanding speaking abilities, students often experience numerous issues, one among which is gender differences. The motive of this research is to conduct studies in analyzing the mastering forms of speaking abilties that are most customarily applied by means of students and finding full-size differences in learning styles of speaking skills based on gender in teaching English. Qualitative descriptive studies is a research layout in this study. From this research review, it changed into found out that male and female students use the identical learning style, however fluctuate in the frequency of using the learning fashion. female students use the visual learning style with a mean of 3.8, while male students with an average of 3.5. The average of female students who use auditory is 4.6, while the common of male students is 3.4. For the common female student who uses kinesthetic is 3.7 but the average male student is 2.8.